Anti Mullerian Hormone Serum Level Indicates Ovarian Response in Controlled Ovarian Hyperstimulation of IVF Cycles - Wiweko, Budi (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To evaluate the clinical value of Anti Mullerian Hormone serum (AMH) level as one of ovarian response indicator in controlled ovarian hyperstimulation in IVF cycles. Method: This cohort-prospective study was conducted in Dr. Cipto Mangunkusumo General Hospital. The subjects of this study were infertile couples who underwent controlled ovarian hyperstimulation in IVF cycles. The measurement of FSH level, estradiol level, AMH level, and antral follicles count was done in the beginning of IVF cycles. The cycles were divided into two groups, good responder group and poor responder group. Good responder group had three or more mature oocytes, while the poor responder group had two or less mature oocytes. Statistical analysis was done using T-Test and Receiver Operator Characteristic area under curve (ROCAUC) to measure the predictive value of AMH, FSH, estradiol, age, and antral follicle count as ovarian response predictors. Results and Discussion: From 92 IVF cycles, there were 15 poor responder cycles (16.3%) and 77 good responder cycles. AMH serum level was 3.75 Â± 2.77 Î¼g/ml in good responder cycles and 1.04 Â± 1.39 Î¼g/ml in poor responder cycles (p < 0.0001). AMH serum level was more superior than other ovarian response predictors (AUC 0.846) with cut-off value of 1.40 Î¼g/ml. AMH serum level â¥ 1.40 Î¼g/ml had good predictive value as ovarian reserve or ovarian reserve parameter with 81% sensitivity and 87% specificity. Conclusion: AMH serum level was more superior ovarian reserve and ovarian response predictor compared to other parameters. [Indones J Obstet Gynecol 2010; 34-3: 114-8] Keywords: anti-Mullerian hormone, ovarian reserve, ovarian response